2020
DOI: 10.3390/ma13030595
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Deposition of Layer-by-Layer Unsheathed Carbon Nanotubes—A Step Towards Steerable Surface Roughness and Wettability

Abstract: It is well known that carbon nanotube (CNT) oxidation (usually with concentrated HNO3) is a major step before the electrophoretic deposition (EPD). However, the recent discovery of the “onion effect” proves that multiwalled carbon nanotubes are not only oxidized, but a simultaneous unsheathing process occurs. We present the first report concerning the influence of unsheathing on the properties of the thus-formed CNT surface layer. In our study we examine how the process of gradual oxidation/unsheathing of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…However, it is of utmost importance that the coating is sufficiently thick to overcome the influence of the substrate and that the wetting behavior of the CNT dominates, as evidenced in the thinner CNT-1 coating. Contrarily, a substrate with higher roughness should be adopted to achieve higher CA, as reported by Korczeniewski et al 55 and Shirtcliffe et al 56 The strong hydrophobic tendencies of CNTs is evidenced in CNT-1. However, the short deposition time did not allow a complete coating of the substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it is of utmost importance that the coating is sufficiently thick to overcome the influence of the substrate and that the wetting behavior of the CNT dominates, as evidenced in the thinner CNT-1 coating. Contrarily, a substrate with higher roughness should be adopted to achieve higher CA, as reported by Korczeniewski et al 55 and Shirtcliffe et al 56 The strong hydrophobic tendencies of CNTs is evidenced in CNT-1. However, the short deposition time did not allow a complete coating of the substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Moreover, observing CNT-1, the conclusion can be drawn that at least 1 μm thickness is required in CNT coatings to achieve superhydrophobic wetting behavior. A previous study by Korczeniewski et al 55 found that the diameter of the CNT agglomerates is crucial to control the wetting behavior of EPDproduced CNT coatings. The authors conclude that smaller CNT agglomerate diameters (measured via dynamic light scattering) and higher substrate roughness correlate to higher CA�with variations of up to 40°.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, prolonging the deposition process (and thus obtaining a thicker coating) could promote super-hydrophobicity in the CNT-coated surfaces. Moreover, a smoother substrate could further increase the CA, improving hydrophobicity [63]. Additionally, Korczeniewski et al previously reported that larger CNT agglomerate reduces CA, however, prolonging dispersion times (homogenization and ultrasound) negatively impacts the structure of the nanotubes [39,64].…”
Section: Wetting Behaviormentioning
confidence: 99%